Long-term risks of childhood surgery - Win, Gunter de; De Kort, Laetitia; Learner, Hazel; Noah, Anthony; Dautricourt, Stephanie; Nijman, Rien; Stein, Raimund (Journal of pediatric urology, 2024)
Introduction - Several patients, who underwent major reconstruction under the care of an experienced pediatric urologist are now, as adults, several years later, appearing with long term problems and complications. This consensus process was undertaken to give an overview of long term consequences (and their management) of urological childhood surgery. - Material and methods - Several known urologists with experience in life-long follow up and revisional surgery of patients with congenital conditions were asked to review literature and comment based on their experience about several complications of childhood surgery. - Results - Renal impairment, metabolic consequences, bladder stones, Vit B 12 deficiency and recurrent infections are often encountered. Also recurrent ureteric strictures and difficulties with catheterizable channel (both obstruction and incontinence) can be challenging to manage. Specific attention is needed regarding female sexuality and pregnancy. Both the development of malignancies in reconstructed bladders as secondary malignancies need to be taken into account during follow up. - Conclusion - Follow up of patients with rare congenital conditions is highly specialized and revisional surgery can be challenging. Therefore, follow up needs to be organized in specialized centers.
Online verfügbar: 17. Juli 2023, Artikelversion: 18. April 2024
Gesehen am 23.10.2024